HUBUNGAN ANTARA PELATIHAN BANK SAMPAH PATRATURA DENGAN SIKAP PESERTA TERHADAP LEMBAGA - Meilianti Rona Asmara; Kokom Komariah; Syauqy Lukman (Universitas Lambung Mangkurat, 2018)
AbstractTraining is a situation which someone gain experiental learning. In achieving the success of a training, there are something which become the determinant aspect, ie curriculum, means, and trainer. In training of bank sampah Patratura, found many problems from every determinants aspect of training success that caused the training felt less than the maximum. This research aimed to find out the correlation between curriculum, means, and trainer with participant’s attitude to the institution ie PT. Pertamina Refinery Unit III. The theory used in this research is Experiental Theory by Pace and Faules. The method used is survey method with correlational research type, through hypothesis tests of Spearman Rank (rs) with descriptive and inferential analysis techniques. The sample size of this research was 43 people selected through simple random sampling techniques. The data collection technique used was using questionnaire, interview and research literature. The results of this research showed that there was a significant correlation between curriculum, means, and trainer with participant’s attitude to the institution. The conclutions of this research showed that there was a significant correlation between training of bank sampah Patratura with participant attitude to the institution.Keyword: Training, Bank sampah, attitude, Institution